Reflective silica-based particles and powders for roofs and building materials and methods of making same

By using the ground silica feed in roofs and building materials, the white silica-based product prepared by mixing and heating the prepared metallic silica feed with sodium silicate and water, the problems of high reflectivity and low cost in the prior art are solved, and the goals of high reflectivity and low cost are achieved.

CN119816470APending Publication Date: 2025-04-11COVIA SOLUTIONS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380061712.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide a material that can meet the reflectivity requirements of roofs and building materials and is also inexpensive.

Method used

By mixing the ground silica feed with sodium silicate and water to form an agglomerated mixture and heating at a temperature of 1300°C to 1550°C, a white silica-based product was prepared, making cubicles dominate the silicon dioxide crystal structure, achieving the goals of high reflectivity and low cost.

Benefits of technology

A white silica-based product with L* values ​​of 93-98 in the CIELAB color space is realized, with high reflectivity and suitable for roofing and building materials, and is at a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816470A_ABST
    Figure CN119816470A_ABST
Patent Text Reader

Abstract

A method for preparing a white silica-based product, such as pellets (e.g., roof pellets), the method comprising: grinding a feed to obtain a ground feed having a size of about 0.5 [mu] m to about 50 [mu] m; mixing the ground feed with an adhesive and water to obtain an agglomerated mixture; and heating the agglomerated mixture at a temperature of about 1350 DEG C to less than about 1550 DEG C for a period of time to produce a white silica-based product. The agglomerated mixture is sufficiently heated to prevailing cristobalite in the silica crystal structure of the white silica-based product, and further to have an L * value of the white silica-based product in the CIELAB color space of 93-98.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention relates to the technical field of silicon dioxide materials, and in particular to reflective silicon dioxide-based particles and powder for roofing and building materials and a preparation method thereof. Background Art

[0001] Mineral particles help maintain the integrity of roofs and other building products in outdoor environments. Specifically, the particles protect roofs and building products from wear and abrasion caused by rain, snow, ice and wind, as well as damage caused by the sun's ultraviolet radiation, and can also serve other purposes, such as providing aesthetic appeal to roofs and reflecting solar energy and light. In some places, building codes require roofs to have certain properties, such as minimum solar reflectance. Mineral powders are added to paints and surface coatings to provide light reflection, thereby improving visibility, for example, as lane and road markings on pavement.

[0002] Various materials have been proposed to provide solar and light reflection, although many of these materials do not meet other requirements for roofing, building and coating materials. In addition, other materials that have been proposed to provide reflectivity are too costly to be used in roofing and other building and coating materials. Summary of the invention

[0003] The present invention discloses a method for preparing a white silica-based product, the method comprising grinding a feed material to obtain a ground feed material having a size of about 0.5 μm to about 50 μm; mixing the ground feed material with a binder (e.g., sodium silicate) and water to obtain an agglomerated mixture; and heating the agglomerated mixture at a temperature of about 1300° C. to less than about 1550° C. for a period of time to obtain a white silica-based product. The agglomerated mixture is heated sufficiently to allow cristobalite to dominate the silica crystal structure of the white silica-based product, and further to allow the white silica-based product to have an L* value of 93-98 in the CIELAB color space.

[0004] In some aspects, the feedstock is derived from waste sand byproducts generated by a sand mill. In some aspects, the binder is present in an amount of about 0.2 wt.% to about 10 wt.%, based on the total weight of the agglomerated mixture, or in an amount of about 1 wt.% to about 5 wt.%, based on the total weight of the agglomerated mixture.

[0005] In certain aspects, the water content is about 10 wt.% to about 20 wt.%, based on the total weight of the agglomerated mixture, or about 12 wt.% to about 16 wt.%, based on the total weight of the agglomerated mixture.

[0006] In certain aspects, the agglomerated mixture further comprises sodium hydroxide.

[0007] In some aspects, the binder and water are applied to the ground feed by spraying. In some aspects, the temperature of the heating comprises heating the agglomerated mixture to about 1350° C. to about 1400° C., and according to some aspects, the heating time is about 40 minutes to about 60 minutes. In some aspects, the heating helps to sinter the particles in the agglomerated mixture into microparticles.

[0008] In certain aspects, the method further comprises cooling the white silica-based product to a temperature of about 100° C. or less. In certain aspects, the method further comprises applying at least one coating on the white silica-based product particles at a temperature of about 75° C. to about 100° C., in other aspects, the method comprises applying at least one coating on the white silica-based product particles at a temperature below 50° C., and in certain aspects, the method further comprises sieving the white silica-based product to select white silica-based particles having an average particle size of about 0.45 mm to about 2.5 mm.

[0009] According to certain aspects, the white silica-based microparticles have a specific gravity of about 2.32 to about 2.40. In certain aspects, the sieving is effective to produce an oversized white silica fraction and an undersized white silica fraction, and the method further comprises mixing the oversized white silica fraction and the undersized white silica fraction; and grinding the mixed fraction to produce a white silica-based powder having a maximum particle size of 325 mesh.

[0010] According to various aspects of the present disclosure, roofing granules include white silica-based particles having an L* value of 93-98 in the CIELAB color space, wherein cristobalite predominates in the silica crystal structure of the white silica-based particles.

[0011] In certain aspects, the roofing granules have an average particle size of about 0.45 mm to about 2.5 mm. In certain aspects, the roofing granules have a specific gravity of about 2.32 to about 2.40. In certain aspects, the roofing granules have a functional coating on the outer surface of the white silica-based particles.

[0012] According to various aspects disclosed herein, a white silica-based microparticle reflects more than 75% of visible light in the wavelength range of 360nm to 750nm and has an L* value of 93-98 in the CIELAB color space; or cristobalite is the main silica crystal structure; or the microparticle has a specific gravity of about 2.32 to about 2.40. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1A is a photograph showing the feed of Sample A described in the Examples;

[0014] Figure 1B is a photograph showing a crude material of Comparative Sample D obtained by heating the sample A feed described in the Example for heat treatment;

[0015] Figure 1C is a photograph showing a microparticle sample E obtained by feeding the sample A described in the example;

[0016] Figure 2 is a photograph showing a microparticle sample F obtained from the sample B feed described in the example;

[0017] Figure 3 is a graph of the reflectance % (Y-axis) as a function of wavelength (X-axis; in nm) for various samples described in the present invention. DETAILED DESCRIPTION

[0018] The present invention provides a white, in some aspects, ultra-white silica product in powder or particulate form, having high reflectivity and suitable for use as roofing granules and as powder for coatings and building materials. Due to its high whiteness and relatively low cost, the ultra-white filler of choice for many products is cristobalite. Although cristobalite used to make artificial products is naturally present, it is usually prepared by heating quartz sand, that is, sand that is essentially silica with a quartz crystal structure, until essentially all of the quartz content is converted to other forms of silica, including cristobalite. Typically, this is achieved by heating the quartz sand to ≥1550°C in a rotary kiln and maintaining it for ≥1 hour, causing the quartz sand to tumble during the process from the inlet to the outlet of the rotary kiln. Thus, an L* value of 97 or higher in the CIELAB color space is obtained, and it contains at least about 85wt.% of cristobalite and less than 1wt.% of quartz based on the total weight of the crystalline silica. The ultra-white quartz product usually also includes a certain amount of amorphous silicon dioxide, usually about 5 wt.% or more of the total weight of silicon dioxide in the ultra-white quartz crystal. However, in order to obtain the ultra-white product, high-quality sand must be used as feed material.

[0019] The present invention provides a method for preparing a white silica-based product, such as granules (e.g., roofing granules), comprising grinding a feedstock to obtain a ground feedstock having a size of about 0.5 μm to about 50 μm; mixing the ground feedstock with sodium silicate and water to obtain an agglomerated mixture; and heating the agglomerated mixture at a temperature of about 1300° C. to less than about 1550° C. for a period of time to produce a white silica-based product. The agglomerated mixture is heated sufficiently to allow cristobalite to dominate the silica crystal structure of the white silica-based product, and further to allow the white silica-based product to have an L* value of 93-98 in the CIELAB color space. The method is capable of using alternative sand as a feedstock to produce a white or ultra-white silica-based product. Silica Feed

[0020] The silica feed subjected to the heat treatment process in the present invention, based on the total weight of the silica contained in the silica feed, generally contains greater than or equal to about 98wt.% of silica, including greater than or equal to 99.5wt.% of silica, wherein about 95% or more of the silica is quartz silica. In the present invention, "quartz silica" refers to silica having a quartz crystal structure. Therefore, the feed generally contains about 93wt.% (~98wt.% x 95% = ~93wt.%), or more, containing 94.5wt.% (~99.5wt.% x 95% = ~94.5wt.%) or more of quartz silica. In various embodiments, the silica feed comes from about 98wt.% to about 99.8wt.% of silica, and from about 93wt.% to about 99wt.% of quartz silica. Thus, while the process described herein utilizes relatively pure quartz silica sand, as discussed above, it should be understood that the process does not require the highest purity quartz silica sand as a feed.

[0021] Quartz sand is typically processed in a series of steps to extract the desired quartz from the coarse impurities. These steps typically include crushing (if hard rock or sandstone), washing, water washing, hydraulic classification and desludging. Flotation may also be required if the ore contains different materials, such as feldspar, garnet and mica. Magnetic separation can also be used to remove magnetic or paramagnetic particles. Thereafter, the cleaned ore is typically dried and sized, usually by bulk dewatering using cyclones and / or blowdown piles, heating to dryness (e.g., less than about 1 wt.% water) and sizing by screens or sieves.

[0022] However, in particular embodiments of the present invention, the feed can be untreated quartz sand, which already has the desired relatively high level of silica purity, or the untreated quartz sand can be easily and inexpensively cleaned, such as by washing, water washing, hydraulic classification, desliming, etc., to achieve this relatively high level of silica purity.

[0023] In the present invention, "untreated quartz sand" is understood to mean naturally occurring free-flowing sand, in which at least 95 wt. % of the silicon dioxide has a quartz crystal structure.

[0024] Furthermore, "naturally occurring" is understood to mean that, prior to the initiation of the thermal treatment process of the present invention, the silica feed material has not been processed to chemically convert it to another material, such as when quartz silica is converted to an alkali metal silicate, an alkoxysilane, or hydrolyzed silica, or physically convert it to another material, such as when particulate silica is converted to silica sol or water glass, or when particulate silica is fired / sintered at a sufficiently high temperature to change the phase structure of the silica from crystalline to amorphous and / or to change the shape of the silica particles to a more spherical shape. Thus, "naturally occurring" means that the particulate product is found essentially in nature, such as beach sand, quarry sand, and sand obtained by crushing sandstone, etc.

[0025] Unless otherwise stated, all particle sizes disclosed herein refer to mesh (US).

[0026] Due to feed variation and measurement accuracy issues, it is understood that "about" related to the above concentrations means that the accuracy of the above values ​​is ±3wt.%, more typically ±2wt.%, ±1wt.%, and even ±0.1wt.% is possible.

[0027] Unless otherwise specified, "white silica-based product" includes white or ultra-white silica-based microparticles disclosed in the present invention, white or ultra-white silica-based powders disclosed in the present invention, or a combination thereof.

[0028] Finally, when referring to untreated quartz sand, "cleaning" and "washing" are understood to mean the removal of non-siliceous components from the surface of the untreated quartz sand particles. This does not mean or include a process of extracting silicon dioxide in the form of water-soluble compounds from the untreated quartz sand particles and then recovering silicon dioxide from the extracted water-soluble compounds.

[0029] In any case, it should be understood that the feed may contain some small amounts of impurities, generally greater than or equal to about 0.2 wt.%, greater than or equal to about 0.5 wt.%, greater than or equal to about 0.6 wt.%, greater than or equal to about 0.7 wt.%, greater than or equal to about 0.8 wt.%, or greater than or equal to about 0.9 wt.%. In addition, in most cases, the feed will not contain greater than 2.0 wt.%, or greater than 1.0 wt.% of these impurities. Thus, in various embodiments, the feedstock may contain, based on the total weight of the material, about 0.2 wt.% to about 2.0 wt.%, about 0.5 wt.% to about 2.0 wt.%, about 0.6 wt.% to about 2.0 wt.%, about 0.7 wt.% to about 2.0 wt.%, about 0.8 wt.% to about 2.0 wt.%, about 0.9 wt.% to about 2.0 wt.%, about 0.2 wt.% to about 1.5 wt.%, about 0.5 wt.% to about 1.5 wt.%, about 0. .6 wt.% to about 1.5 wt.%, about 0.7 wt.% to about 1.5 wt.%, about 0.8 wt.% to about 1.5 wt.%, about 0.9 wt.% to about 1.5 wt.%, about 0.2 wt.% to about 1.0 wt.%, about 0.5 wt.% to about 1.0 wt.%, about 0.6 wt.% to about 1.0 wt.%, about 0.7 wt.% to about 1.0 wt.%, about 1.8 wt.%, or about 1.8 wt.%, including all ranges and sub-ranges of impurities.

[0030] In a specific embodiment, the silica feed is untreated quartz sand with a particle size of 30 to 170 mesh (US). However, feeds with other particle sizes can also be used. Therefore, the silica feed can have a gravel particle size of 2.5 to 8 mesh (US), a coarse sand or coarse sand particle size of 8 to 70 mesh (US), or a fine sand particle size of 70 to 170 mesh (US). According to a specific specific embodiment, a silica feed with a particle size of 140 to 200 mesh (US) can also be used. It should be understood that the grinding method described below can use silica feeds with a variety of particle sizes.

[0031] In various embodiments, waste sand fractions commonly found in various sand plants can be used as feed. Many industrial sand plants are in operation to produce sand grades of different particle sizes and / or particle size distributions for the manufacture of different products, such as glass, proppant, play sand, concrete sand, etc. Therefore, in the manufacture of commercial products, high-quality, high-purity sand fractions of particle sizes with limited commercial interest are often produced as by-products. These sand fractions are either not all used or, in some cases, must be discharged to waste, such as by burying them underground or otherwise returning them to the mine, beach or other geological location where they were originally obtained. Therefore, these sand fractions, hereinafter referred to as "waste sand by-products", either have no value at all or, more commonly, have a negative value due to the cost of discharging them to waste.

[0032] In various embodiments, the feed is subjected to a grinding step. In the grinding step, the feed is ground to a maximum particle size of about 325 mesh. Grinding can be performed using any suitable equipment and procedures known and used in the art. In a specific embodiment, grinding is effective to form angular powder particles having an average particle size of about 10-15 μm. For example, grinding can be effective to produce particles having a particle size of about 0.5 μm to about 50 μm.

[0033] After grinding, the ground feed is mixed with a binder and water in an agglomeration step. In various embodiments, in the agglomeration step, the ground feed can be combined with water and a binder, a flux, or both a flux and a binder. In various embodiments, the binder is a sodium-containing binder, such as but not limited to sodium silicate. In a specific embodiment, the flux is a sodium-containing flux, such as sodium hydroxide. Without being bound by theory, it is believed that certain binders, such as sodium silicate, can act as both a binder (e.g., to bond particles to each other) and a flux (e.g., to change the crystal structure of silicon dioxide from quartz to cristobalite and / or tridymite under relatively low thermal conditions). In a specific embodiment, the binder is present in an amount of about 0.2 wt.% to about 10 wt.% based on the total weight of the final product. For example, the binder content can be about 0.5 wt.% to about 10 wt.%, about 0.5 wt.% to about 7.5 wt.%, about 0.5 wt.% to about 5.0 wt.%, about 1.0 wt.% to about 10 wt.%, about 1.0 wt.% to about 7.5 wt.%, about 1.0 wt.% to about 5.0 wt.%, about 1.5 wt.% to about 10 wt.%, about 1.5 wt.% to about 7.5 wt.%, about 1.5 wt.% to about 5.0 wt.%, about 2.0 wt.% to about 10 wt.%, about 2.0 wt.% to about 7.5 wt.%, about 2.0 wt.% to about 5.0 wt.%, about 2.5 wt.% to about 10 wt.%, about 2.5 wt.% to about 7.5 wt.%, or about 2.5 wt.% to about 5.0 wt.%, including any values ​​within all sub-ranges of ranges.

[0034] Based on the total weight of the final product, the water content can be about 10wt.% to about 20wt.%. For example, the water content can be about 10wt.% to about 20wt.%, about 11wt.% to about 18wt.%, or about 12wt.% to about 16wt.%, including any value in all ranges and sub-ranges. Water can be added to the agglomerated mixture as a separate component, as part of a binder (e.g., when the binder is added in an aqueous form), or as a combination thereof. For example, in a specific embodiment, a binder is added in the form of a 40wt.% aqueous solution of active sodium silicate, and auxiliary water is also added to the milled feed.

[0035] Although not limited by any particular method, in various embodiments, by spraying or pouring the aqueous binder of dilution in a granulator, including but not limited to the Eirich mixer, binder and water are applied to the feed after the grinding. No matter how the application method is, the feed, binder and water after the grinding are mixed and granulated to form a mixture of agglomeration, sometimes referred to as particles in this article. In other embodiments, water and binder, fluxing agent or binder and fluxing agent are applied to the feed after the grinding and mixed to form particles. Although agglomeration can be carried out according to any suitable method known in the art and used, in various embodiments, agglomeration can be carried out at ambient temperature. Heat treatment method

[0036] According to various specific embodiments, the agglomerated mixture (ie, particles) flows into a rotary kiln where it is heated for a time and temperature sufficient to convert the crystal structure of its bulk silica content from quartz to cristobalite.

[0037] As previously mentioned, the use of heat to convert quartz to cristobalite has been practiced in the industry for many years. In various embodiments, a similar heating process is performed, but the energy required is significantly reduced because significantly lower processing temperatures and significantly shorter processing times are used. According to various embodiments, it has been found that white or ultra-white silica-based products can be obtained by this method, even though much less thermal energy is used, and the whiteness level thereof is close to, and in some cases equal to, the whiteness level exhibited by industrially produced cristobalite.

[0038] Thus, various embodiments provide a white or ultra-white silica-based product as a replacement that is substantially as good as, or even just as good as, industrial cristobalite in many applications, but at a significantly lower cost.

[0039] Thus, in various embodiments, the agglomerated mixture is heated to a temperature of no more than about 1550°C for no more than about one hour (i.e., about 60 minutes). In certain embodiments, the agglomerated mixture is heated to a temperature of about 1300°C to about 1550°C, about 1325°C to about 1550°C, about 1350°C to about 1550°C, or about 1375°C to about 1550°C for a time of about 40 minutes to about 60 minutes. Although the temperature may vary according to a particular embodiment, in general, the temperature may be high enough to obtain a silica composition that is primarily cristobalite. However, it is believed that grinding the feed sand will produce particles that can be converted to cristobalite at a lower temperature than required by conventional methods. In addition, the temperature is sufficient to sinter the particles into bonded particles, thereby providing mechanical integrity to the particles. For example, the heating may be performed in a continuous manner in a rotary kiln, but other heating methods may also be considered.

[0040] Thereafter, the white or ultra-white silica-based product is cooled to a temperature of about 100°C or less, a temperature of about 95°C or less, a temperature of about 75°C or less, a temperature of about 50°C or less, or to room temperature (e.g., about 23°C). In a specific embodiment, the white or ultra-white silica-based product can be cooled by an air quenching process that uses forced convection of ambient air to accelerate cooling. In certain specific embodiments, one or more coatings can be applied during the cooling process. For example, a waterproof or other functional coating can be applied to the white or ultra-white silica-based product when the white or ultra-white silica-based product is at a temperature of about 75°C to about 100°C, and the coated silica can then be cooled to room temperature. As another example, a functional coating can be applied to the white or ultra-white silica-based product when the temperature of the white or ultra-white silica-based product is below 50°C. For example, a functional coating can be applied to the white or ultra-white silica-based product at a temperature of about 15°C to about 50°C. White silica based microparticles

[0041] In various embodiments, the white or ultra-white silica-based product can be sieved to select particles with a specific size. Screening can be performed by any suitable method known and used in the art, including but not limited to using a vibrating screen. In various embodiments, the selected microparticles have a particle size based on -8 / +35 mesh. In certain embodiments, the average particle size that the microparticles have is about 0.45mm to about 2.5mm. However, in other embodiments, depending on the specific application, particles with larger or smaller particle sizes can be used. For example, when particles are intended to be used for roof applications (for example, applied to the surface of a roofing board or a flat roof), particles with a standard size #11 particle size or another standard size commonly used in the roofing industry can be selected. In other applications, for example, when particles are used as fillers for pigments, coarser or finer particles can be used. As will be described in more detail below, in certain embodiments, particles with coarser and / or finer particle sizes than a particular embodiment can be further processed.

[0042] The white or ultra-white silica-based microparticles are generally round in shape, although it is envisaged that the agglomeration process described above may be modified to obtain microparticles having other shapes.

[0043] The white or ultra-white silica-based microparticles have a bulk density of less than about 75 lb / ft 3 For example, in various embodiments, the white or ultra-white granular silica-based filler has a bulk density of about 30 lb / ft 3 About 75 lb / ft 3, about 35lb / ft 3 to about 75lb / ft 3 , about 40lb / ft 3 to about 75lb / ft 3 , about 45lb / ft 3 to about 75lb / ft 3 , or about 50 lb / ft 3 to about 75lb / ft 3 In contrast, conventional pellets of similar size have a mass of approximately 80 lb / ft 3 About 120 lb / ft 3 In various embodiments, the white or ultra white granular silica-based filler has a specific gravity (by helium pycnometry) of about 2.32 to about 2.40, depending on the temperature and residence time during the heat treatment. This is in contrast to the specific gravity of the feed of a particular embodiment of about 2.65. Specific gravity measurements of the particles by water pycnometry showed that the specific gravity of the particles was reduced by about 20% compared to the feed, indicating that there is significant void volume within the particles prepared by this method.

[0044] As previously described, the white or ultra-white silica-based microparticles exhibit very high L* values, close to, and in some cases equivalent to, the L* values ​​of industrial cristobalite, despite the fact that the heat treatment conditions used to prepare it are significantly less harsh than the heat treatment conditions used to prepare industrial cristobalite. In various embodiments, the white or ultra-white silica-based microparticles exhibit an L* value of about 93 to about 98, such as about 94 to about 97, about 94 to about 98, about 95 to about 98, about 96 to about 98, about 93 to about 97, about 93 to about 96.5, about 93 to about 96, about 93 to about 95, or about 95 to about 96.5. In addition, in various embodiments, the white or ultra-white silica-based microparticles exhibit an average visible light reflectance of about 75% to about 85%, such as about 77% to about 83% or about 79% to about 82%. White silica based powder

[0045] As described above, in various embodiments, the white or ultra-white silica-based product is sieved to select white or ultra-white silica-based particles of a specific size. Thus, in addition to the selected white or ultra-white silica-based particles, an oversized white or ultra-white silica fraction (e.g., particles having a particle size greater than 8 mesh or about 2.5 mm) and an undersized white or ultra-white silica fraction (e.g., particles having a particle size less than 35 mesh or about 0.45 mm) are also produced.

[0046] Therefore, in some embodiments, after heat treatment and screening, the oversized white or ultra-white silica portion and the undersized white or ultra-white silica portion are combined for further processing. Similar to the white or ultra-white silica-based particles described above, the oversized white or ultra-white silica portion and the undersized white or ultra-white silica portion are mainly cristobalite and have a specific gravity (by helium specific gravity) of about 2.32 to about 2.40, depending on the temperature and residence time during the heat treatment process. The combined portion can then be ground or milled to produce a powder with a minimum particle size of 325 mesh. Grinding or milling can be performed according to any method known and used in the industry, and can be the same or different from the grinding or milling method used before heat treatment. For example, in some embodiments, the combined portion is ground using a ball mill with alumina media so that the particle size distribution is less than about -325 mesh for about 97% of the powder obtained after grinding. The maximum size of the white or ultra-white silica-based powder can be less than 325 mesh using conventional air classification. In other words, in various embodiments, the white or ultra-white silica-based powder has a particle size of about 44 microns or less.

[0047] In certain embodiments, the aforementioned ground particles can be used as a substitute or filler for one or both of the white or ultra-white silica parts to produce the white or ultra-white silica-based powder. For example, after screening, the selected particles can be ground using a ball mill to produce a white or ultra-white silica-based powder. In other embodiments, the screening step can be omitted, and a ball mill can be used to grind the white or ultra-white silica-based product to produce a white or ultra-white silica-based powder.

[0048] The white or ultra white silica-based powder can be used in a variety of applications, including as a filler or as a feed to another granulation process. Other applications are also contemplated and are well known in the art. Man-made products

[0049] The white or ultra-white silica-based particles and / or the white or ultra-white silica-based powder can be used to prepare a wide variety of different man-made products, including solid shaped articles as well as adhesives, sealants, coatings and mastics.

[0050] Examples of solid formed products include engineered stone for making synthetic kitchen countertops, artificial rocks for finishing fireplaces and building exteriors, tiles, bricks and white architectural concrete. Such products typically contain one or more fillers or aggregates and at least one or more binders, which may be cement, resin or both. The white or ultra-white silica-based products (powders or particles) can replace these fillers and / or aggregates. Portland cement (typically including whitening agents such as titanium dioxide, calcium carbonate or cristobalite) is the most common binder, although other binders, including pozzolan-based binders, other hydraulic lime-based cements, etc., may also be used. In addition, in some embodiments, white or ultra-white silica-based particles can be used as particles on roof tiles. For example, compared to conventional standard roof particles, the white or ultra-white silica-based particles can be used as specific particles on roof tiles to provide higher solar reflectivity. Additionally or alternatively, the white or ultra-white silica-based particles and powders can be used to replace fillers used in asphalt or other building products such as siding, paving and architectural coatings. Reflective powders can be added to paints and coatings for use as lane markings and other markings on road surfaces.

[0051] According to various embodiments, the white or ultra-white silica-based products may be used to replace some or all of these conventional silica-based products, as such materials have been found to function just as well as these materials in terms of physical properties of manufactured products at a potentially lower cost, depending primarily on the degree of whiteness desired and other factors such as raw material supply, location, shipping costs, etc. In addition, because the L-values ​​of the white or ultra-white silica-based products of the present invention approach and are sometimes equal to the L-values ​​of conventionally formed industrial cristobalite, further advantages in product appearance may be achieved by this approach. Example

[0052] The following examples are for illustration only and are not intended to limit the general inventive concepts described herein.

[0053] Example 1

[0054] First, the optical properties of various feeds were recorded. Feed Sample A was chemically (dirty) untreated coarse sand (e.g., containing greater than 2 wt.% contaminants). Feed Sample B was -100 mesh sized sand, of which 99 wt.% was SiO2. Feed Sample C was SILVERBOND 325 ground crystalline silica, a high purity quartz raw material commercially available from Covia, containing approximately 99.5 wt.% SiO2 and ground to -325 mesh size. The optical properties of the dried material were measured using an X-Rite 9600 reflectance spectrophotometer using an optical glass cuvette with a diameter of 25 mm. The results are listed in Table 1, and the bulk density (loose) was determined according to ASTM C-29 in grams per milliliter (g / mL).

[0055] Table 1:

[0056] Comparative Sample D was prepared by subjecting Feed Sample A to a heat treatment. Specifically, a certain amount of Sample A sand was mixed with 0.2 wt.% sodium hydroxide and heated to 1525°C in a rotary kiln for 60 minutes to convert SiO2 from quartz to cristobalite without first grinding and agglomerating Feed Sample A into particles. Optical properties and bulk density were measured as described above and are reported in Table 1. Photographs of Sample A and Comparative Sample D are shown in Table 1. Figure 1A and 1B shown.

[0057] like Figure 1A and 1B As shown, black specks appeared in the coarse cristobalite sand after heat treatment. It is believed that these black specks are iron oxide, which appears yellow in feed sample A, but becomes black specks due to changing from one form to another during heating. Mica and other minerals present as contaminants in the sample A feed also appear as specks and are present as black specks in comparative sample D. Therefore, although the cristobalite itself appears white and brighter compared to the feed material, the black specks may make the product unsuitable for its intended use. Simply heating the feed will not reduce the appearance of black specks.

[0058] Next, samples E, F and G were prepared by granulating the feed samples A, B and C, respectively. In particular, a certain amount of samples A, B and C were ground to about -325 mesh, equivalent to a range of about 0.5μm to 50μm, with an average particle size of about 10-15μm, granulated with 5wt.% water glass (40% sodium silicate), and fired in a rotary kiln at 1350°C for 60 minutes. Samples E and F were granulated using laboratory-grade granulation equipment, while sample G was granulated using an Eirich granulator. The optical properties and bulk density were measured as described above and are reported in Table 2. Photographs of granulated samples E and sample F are shown below, respectively. Figure 1C and Figure 2shown.

[0059] Table 2:

[0060] Compare Figure 1C and Figure 1B , it can be seen that grinding and agglomeration can effectively eliminate the appearance of black specks in the particles. For sample E, the treatment increased the brightness of the product (e.g., increased the L* value) and the brightness of the product compared to both comparative sample D and feed sample A. Similarly, the treatment effectively increased the brightness (L* value) and brightness of samples F and G compared to feed samples B and C, respectively. Therefore, the values ​​in Table 2 show that the method described herein can effectively prepare a product without black specks and is brighter than the feed that has not been cleaned or decontaminated.

[0061] In addition, Figure 1C and Figure 2 1 and 2, it can be seen that, although the material of Sample F is brighter than that of Sample E, the feedstock used to prepare Sample F was of higher quality than that used to prepare Sample E. However, the resulting particles of Sample E exhibited L* values ​​greater than 92, indicating that these particles are at least comparable to conventional solar reflective roofing particles.

[0062] Although the granulation process significantly reduced the bulk density of samples EG compared to the feed of samples AC, it is believed that the bulk density of samples E and F may be very low due to the use of a laboratory granulation process rather than a commercial grade granulator like sample G.

[0063] In addition to the L*, a*, and b* values, the average visible light reflectance of each sample was measured over the wavelength range of 360nm to 750nm. The reflectance % (Y) axis is a function of the wavelength (X axis), such as Figure 3 The average visible light reflectance of each sample is reported in Table 3.

[0064] Table 3: sample Average visible light reflectance Sample A 40.1 Comparative sample D 74.0 Sample E 79.8 Sample B 61.2 Sample F 80.5 Sample C N / A Sample G 91.3

[0065] As shown in Table 3 and Figure 3 As shown, the average visible light reflectance between the granular materials in comparative samples E and F is significantly higher than that of feed samples A and B ( Figure 3 ). The average visible light reflectance of the unground and ungranulated comparative sample D is significantly lower than that of the granulated samples E and F. Sample G shows the highest average visible light reflectance, which can be attributed to the use of a commercial grade granulator. It is believed that the commercial grade equipment used to prepare sample G provides rounder and more consistent particles than the laboratory grade equipment used to prepare samples E and F.

[0066] Example 2

[0067] Next, the amount of sodium silicate was varied to further investigate the effect of the flux on the quartz product. For each sample, 5 pounds (2268 g) of quartz silica powder with an average particle size of 325 μm was loaded into the Eirich mixer, and an appropriate amount (see Table 4) of industrial grade sodium silicate (40% solution) was weighed into a 500 mL measuring cylinder. Fill the measuring cylinder to 500 mL with distilled water and add the contents of the measuring cylinder to the Eirich mixer. Turn off the Eirich mixer, switch it to the "low speed" state for about one minute, and then switch it to the "high speed" state for about two minutes. Next, turn off the center blade and allow the bowl to rotate for another minute. Then, add about 125 g of additional quartz silica powder, let the bowl rotate for another minute, and then remove the mixture from the mixer.

[0068] Table 4:

[0069] The mixture was dried overnight in a convection oven with a blower running, but without using any heat. The resulting mixture was sieved to obtain particles with a particle size of -8+35 (i.e., greater than 35 mesh and less than 8 mesh). Approximately 250 g of the sieved particles were loaded into a platinum dish and placed in a box furnace set to a predetermined temperature (see Table 5) for one hour. The dish was then removed from the furnace and cooled to room temperature.

[0070] Table 5:

[0071] As shown in Table 5, for a concentration of sodium silicate above 8 wt. % and at each temperature between 1300° C. and 1400° C., the L* value is 93-98, the a* value is 1.0 to 1.6, the b* value is between 3.3 and 4.8, the brightness is greater than 79, and the specific gravity is from about 2.32 to about 2.40.

[0072] X-ray powder diffraction (XRPD) analysis was performed on each sample in Table 5 to determine the morphology of the resulting particles. Each sample was divided into three (3) portions, each weighing 4 g. Each portion was mixed with 20 wt.% (1 g) of corundum powder and ground to ensure optimal particle size distribution. A Phillips X'Pert Pro PW3040 diffractometer equipped with a variable divergence slit was set to 16 mm exposure area, 15 mm incident beam mask and primary and secondary Soller slits of 0.04 radians. The samples were loaded into a sample holder with an inner diameter of 27 mm. Measurements were made in Bragg-Brentano geometry using continuous scan mode on a rotating sample holder (8 rpm) using Cu-Kα radiation (40 kV and 40 mA, with a step size of 0.026° 2θ in the range of 5 to 64° 2θ and a total measurement time of 62 minutes.

[0073] The BGMN program was used for Rietveld refinement using the Profex graphical user interface. The BGMN program is described in more detail by J. Bergman et al. in "BGMN - A new basic parameter based Rietveld program for laboratory X-ray sources for quantitative analysis and structural studies", CPD Newsletter 20, no. 5 (1998): 5-8, the entire contents of which are incorporated herein by reference. The structural parameters of the analyzed phases were obtained from the Crystallographic Open Database and the BGMN structure file library. For each identified phase, the lattice, peak broadening parameters and preferred orientation (if necessary) were refined within physically acceptable parameter ranges. Corundum was used as an internal standard to approximate the proportion of amorphous matter in the sample.

[0074] XRPD analysis was performed three times and the average weight percent of each of cristobalite, quartz, tridymite, and amorphous silica based on the total amount of silica in each sample is provided in Table 6.

[0075] Table 6:

[0076] As shown in Table 6, heat treating the sodium silicate composition at a temperature range of 1300°C to 1400°C is sufficient to convert the crystallized quartz material to silicon dioxide that primarily includes cristobalite (e.g., the content of cristobalite is greater than 60 wt.%, based on the total weight of silicon dioxide). Each sample also includes less than 5 wt.% quartz (minimum less than 1 wt.% or even less than 0.5 wt.%), 2 wt.% to 22 wt.% tridymite, and 15.5 wt.% to 25 wt.% amorphous silicon dioxide, based on the total weight of silicon dioxide. Although the sample containing 2 wt.% sodium silicate treated at 1300°C (Formulation 1) contains about 3.8 wt.% quartz, it has been demonstrated that increasing the amount of sodium silicate, increasing the temperature, or both, is sufficient to convert greater than 99 wt.% quartz. However, for all samples tested, cristobalite is the predominant crystalline form.

[0077] Typically, the common commercial term refers only to the crystalline portion of the roofing material; in this case, the cristobalite portion of the crystalline silica content of all tested samples was greater than 73%, and in the samples formed using 2%, 4% and 6% sodium silicate, the cristobalite content ranged from 85.3% to 96.6% of the sample crystalline content, as shown in Table 7.

[0078] Table 7:

[0079] The strength of the particles was also tested. The particles were prepared as described in Table 4 above, screened to obtain particles with a particle size of -8+35, and calcined at a temperature of 1300°C, 1350°C, or 1400°C. Then, about 20g of each sample was measured and distributed to the bottom of the crushing unit using a crushing unit funnel. The plunger was inserted into the bottom of the pool and allowed to float downward. The loaded extrusion unit was then placed on the lower platen and the extrusion unit was placed on top of the extrusion unit plunger. The Monogram desktop controller was then turned on and weighed, and the lever was then pumped until the load cell contacted the upper platen. The lever was then pumped until the controller displayed a force of 1,000lbs. The sample was subjected to this force for five (5) minutes; during the 5 minutes, the lever was gently tapped as needed to maintain a force between 1,000lbs and 1,050lbs, and when the timer expired, the force was removed and the extrusion unit was carefully opened.

[0080] The sample was poured onto a #35 mesh screen with a solid disk at the bottom. The screen was placed on a screen shaker at speed five (5) for one (1) minute and rotated as needed to ensure good coverage of the sample on the screen. The sample on the screen was then discarded and the weight of the fines in the solid disk was measured and recorded. Each sample was repeated three times and the average percentage of fines produced is shown in Table 8 below. The percentage of fines produced was calculated by dividing the mass of fines by the initial sample mass and multiplying by 100.

[0081] Table 8:

[0082] As shown in Table 8, regardless of the calcination temperature, the percentage of fine particles resulting from particle crushing decreases with increasing amount of sodium silicate, indicating that increasing amount of sodium silicate results in stronger particles.

[0083] Although only a few embodiments of the present invention have been described above, it should be understood that many modifications may be made without departing from the spirit and scope of the present invention. All such modifications are included within the scope of the present invention, and the present invention is limited only by the appended claims.

Claims

1. A method for preparing a white silica-based product, the method comprising: grinding the feed material to obtain a ground feed material having a size of about 0.5 μm to about 50 μm; mixing the ground feed with sodium silicate and water to obtain an agglomerated mixture; and The agglomerated mixture is heated at a temperature of about 1300° C. to less than about 1550° C. for a period of time to prepare a white silica-based product, wherein the agglomerated mixture is heated sufficiently to allow cristobalite to dominate the silica crystal structure of the white silica-based product, and further to allow the white silica-based product to have an L* value of 93-98 in the CIELAB color space.

2. The method according to claim 1, wherein: The feed material is derived from waste sand by-product generated by a sand plant.

3. The method according to claim 1 or claim 2, wherein: The sodium silicate is present in an amount of about 0.2 wt. % to about 10 wt. %, based on the total weight of the agglomerated mixture.

4. The method according to any one of claims 1 to 3, wherein: The sodium silicate is present in an amount of about 1 wt. % to about 5 wt. %, based on the total weight of the agglomerated mixture.

5. The method according to any one of claims 1 to 4, wherein: The water content is about 10 wt.% to about 20 wt.% based on the total weight of the agglomerated mixture.

6. The method according to any one of claims 1 to 5, wherein: The agglomerated mixture also includes sodium hydroxide.

7. The method according to any one of claims 1 to 6, wherein: The sodium silicate and the water are applied to the ground feed by spraying.

8. The method according to any one of claims 1 to 7, wherein: The heating includes heating the agglomerated mixture to a temperature of about 1350°C to about 1400°C.

9. The method according to any one of claims 1 to 8, wherein: The heating time is about 40 minutes to about 60 minutes.

10. The method according to any one of claims 1 to 9, wherein: The heating helps to sinter the particles in the agglomerated mixture into microparticles.

11. The method according to any one of claims 1 to 10, wherein: The method further includes cooling the white silica-based product to a temperature of about 100° C. or less.

12. The method according to any one of claims 1 to 11, wherein: The method further comprises applying at least one coating on the white silica-based product particles at a temperature of about 75°C to about 100°C.

13. The method according to any one of claims 1 to 11, wherein: The method further comprises applying at least one coating on the white silica-based product particles at a temperature below 50°C.

14. The method according to any one of claims 1 to 13, wherein: The method further comprises sieving the white silica-based product to select white silica-based microparticles having an average particle size of about 0.45 mm to about 2.5 mm.

15. The method according to claim 14, wherein: The sieving is effective to produce an oversized white silica fraction and an undersized white silica fraction, the method further comprising: mixing the oversized white silica portion and the undersized white silica portion; and The mixed parts were ground to prepare a white silica-based powder having a maximum particle size of 325 mesh.

16. The method according to any one of claims 1 to 15, wherein: The white silica-based microparticles have a specific gravity of about 2.32 to about 2.

40.

17. A roofing granular material, wherein: The roofing granules include white silica-based microparticles having an L* value of 93-98 in the CIELAB color space, wherein cristobalite dominates the silica crystal structure of the white silica-based microparticles.

18. The roofing granules of claim 17, wherein: The roofing granules have an average particle size of about 0.45 mm to about 2.5 mm.

19. The roofing granules according to claim 17 or 18, wherein The roofing granules have a specific gravity of about 2.32 to about 2.

40.

20. The roofing granules according to any one of claims 17 to 19, wherein The roofing granules have a functional coating on the outer surface of the white silica-based particles.

21. A white silica-based particle, wherein: Reflects greater than 75% of visible light in the wavelength range of 360nm to 750nm and includes at least one of the following: An L* value of 93-98 in the CIELAB color space; or cristobalite is the predominant silica crystal structure; or The microparticles have a specific gravity of about 2.32 to about 2.40.